Type 2 Diabetes Mellitus and its Relationship with Obesity - Lina Neri Espinosa Pire; Iruma Alfonso González; Michelle Ariana Calvache Vargas; Holger Alexander Lozano Ati (Revista Finlay)
Diabetes mellitus and visceral obesity are two closely related diseases, which are currently considered modern epidemics due to their high incidence, prevalence, complications and the economic expense they generate. An updated descriptive bibliographic review was carried out on diabetes mellitus and its relationship with obesity. Metasearch engines such as: Accessss, SUMSearch 2 and Epistemonikos were used and various databases such as: Pubmed, INASP, Cochrane, Karger, Embase, PsycINFO and LILACS. 18 bibliographic references were selected. The insulin resistance observed in diabetic patients with obesity is caused by inflammation and the presence of immune cells in adipose tissue. In the latter, substances such as leptin and resistin are secreted that increase insulin resistance. The decrease in sensitivity in the liver, skeletal muscle and fatty tissue produces hypoinsulinism and hyperglycemia through compensatory mechanisms. One of the main causes of type 2 diabetes mellitus is obesity, which generates a state of lipotoxicity in multiple organs, which initially decreases insulin sensitivity in the tissues and culminates in the deterioration of β-cell function. of the pancreas.